INDEPENDENCE OF CENTRAL BANK: NEW CHALLENGES - V. Kyrylenko; I. Kulaga; O. Tkachenko; D. Khokhych (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The studydeals with determining the status of central banks and their formal independence in the context of the index approach. The authors argue that there is an inverse relationship between inflation and the level of independence of central banks. It turned out that the expansion of powers of the central bank based on the GMT-index shows a lower level of independence. The authors conducted a quantitative study of the elements of the index of independence of central banks. The peculiarities of formulating the central bank's mandate, procedures for agreeing goals, appointing management and duration of its stay in an office, ability to choose and apply monetary instruments, procedures for covering operating costs of the central bank and transferring profits to the budget, correct interpretation of legislation are identified. The problems of the index approach are the interpretation of the central bank's mandate, the density of the relationship between indices and inflation rates, as well as the quantification of legislation. To eliminate the shortcomings of the basic index approach, alternative approaches are proposed, in particular, the index of constitutional independence, the TOR index and the index of political vulnerability of the management. Extrapolating the index approach for developed countries does not always work when the sampling expands to include emerging market countries. Particularlyin countries with weak institutions, the de facto independence of the central bank does not always correspond to the formal one. For example, in Ukraine, asserting the consistency of the relationship between the inflation rate and the level of formal independence is quite complicated. Particular attention is paid to the problem of opposition to the political and economic independence of the central bank. The originality of the article is due to the need to identify new challenges to the independence of monetary authorities due to macroeconomic and institutional factors that lead to imbalances between the status of central banks and the consolidation of monetary objectives (instruments) at the legislative level to achieve price stability.